The Influence of Problem Based Learning on Students' Science Process Skills: Pengaruh Pembelajaran Berbasis Masalah Terhadap Keterampilan Proses Sains Siswa - Qaseem Zainy (ASIAN: Indonesian Journal of Learning Development and Innovation, 2023)
This research aims to determine the influence of problem-based learning on students' science process skills in the topic of environmental pollution at Saadallah Wannous School. The research method used is Quasi Experimental Design, specifically employing the nonequivalent control group design. The population of this study consists of 7 classes with a total of 300 students. The sampling technique used is Cluster Random Sampling, which resulted in the selection of two classes for the research: Class A as the experimental group and Class B as the control group. The research instrument used is a test consisting of essay questions. The data collection technique used in this study involved conducting tests. The results of this study indicate that problem-based learning has a significant influence on students' science process skills in the topic of environmental pollution